Effect of V Addition on Microstructure and Properties of Cu-1.6Ni-1.2Co-0.65Si Alloys - Jinfeng Zou; Jianyi Cheng; Guangbo Feng; Jian Xie; Fangxin Yu (Metals, 2019)
To obtain high strength and high electrical conductivity at the same time, the microstructure and properties of 0.2 wt.% V-added, 0.1 wt.% V-added and V-free Cu-1.6Ni-1.2Co-0.65Si(-V) alloys were investigated. We examined with electrical conductivity and hardness measurements, tensile test, optical microscope and transmission electron microscope (TEM). The results show that Cu-1.6Ni-1.2Co-0.65Si-0.1V alloy obtains excellent combination properties: electrical conductivity is 46.12% IACS, hardness is 293.88 Hv, and tensile strength is 782 MPa, which are produced by 65% cold rolling + aging at 500 °C for 480 min. The addition of vanadium (V) can accelerate the precipitation of solute atoms from the copper matrix, improve the hardness and electrical conductivity of Cu-1.6Ni-1.2Co-0.65Si alloys, and greatly accelerated the aging response. δ-(Co,Ni)2Si and β-Ni3Si phases are detected in Cu-1.6Ni-1.2Co-0.65Si-0.1V alloy. The Orowan mechanism and grain boundary strengthening play a major role in the yield strength strengthening due to δ-(Co,Ni)2Si phase.